Security Situation in Tesinsko during the Third Republic in the Light of Commemorative Records of National Security Corps' Stations - Kolar, Ondrej (Historica Olomucensia, 2015)
The study deals with aspects of security forces in the nationally mixed region of Tesinsko from the restoration of Czechoslovak administration in the spring 1945 to first months of the Communist regime in 1948. Based on a comparison of ``official'' history recorded in commemorative administrative records, the text describes not only a development of the regional security situation but also gradual politicization and ideologization of police service under the influence of the Communist Party.In the immediate post-war period, it is possible to observe a large degree of personal as well as structural continuity with the era before the year 1938. The principal tasks of the security corps were activities connected with the expulsion of Germans, investigation of war crimes and collaboration. The prime security-political concern was a Czech-Polish tension, which partially calmed down after concluding a treaty between both states in 1947. Criminal cases were recorded only fragmentarily and in the same spirit it may be supposed a certain belittlement of excesses related to soldiers of Czechoslovak and Soviet armies. As commemorative records suggest, references about interwar period were gradually forced out and after February 1948, one can notice complete ideologization and uniformity of chronicle records.
Keywords: National Security Corps; Third Czechoslovak Republic; Tesinsko; expulsion of Germans; Czech-Polish relations; Communism